The Impact of Early Childhood Nutritional Status on Cognitive Development : Does the Timing of Malnutrition Matter? - Glewwe, Paul; King, Elizabeth M. (Washington, DC: World Bank, 2014)
This article uses longitudinal data from the Philippines to examine whether the timing of malnutrition in early childhood is a critical factor in determining subsequent cognitive development. Although some observers have argued that the first six months of life are the most critical in the sense that malnutrition during that time period harms cognitive development more than malnutrition later in life, analysis of the Philippines data does not support this claim. To the contrary, the data suggest that malnutrition in the second year of life may have a larger negative impact than malnutrition in the first year of life.